Occupational health physicians and the impact of the Great Recession on the health of workers: a qualitative study - Mattei, Giorgio; Ferrari, Silvia; Giubbarelli, Giuseppe; Pingani, Luca; Urraci, Gian Mario; Rigatelli, Marco; Galeazzi, Gian Maria (La Medicina del Lavoro, 2015)
Background: Italy is one of the Eurozone members where the 2008 “Great Recession” struck worst, with a 9% drop in national GDP between 2008 and 2013. The negative effects of the recession on the health of the Italian population were documented on a nation-wide level. However, few local or regional studies are currently available in the scientific literature. Objectives: To assess the impact on workers’ health of the economic recession in the industrial area of Sassuolo (Modena, Northern Italy), and to provide recommendations for targeted interventions. Methods: Two focus groups were conducted, involving 8 occupational health physicians (OHPs) active in the area. Rough descriptions were analyzed using MAXQDA 11, according to the principles of grounded theory. Results: 261 segments were coded, divided into four areas. The first, “changes in contemporary world”, pointed out that the recession may have just made pre-existing problems worse, accelerating reductions in staff and workers’ benefits. The second, “social area”, highlighted a decrease in vertical social capital and the beginning of new trends in emigration. The third, “work area”, covered workers’ fear of losing their jobs if they were ill and a reduction in horizontal social capital, namely difficult relations between co-workers. The fourth, “medical area”, indicated a general worsening of workers’ health in the Sassuolo ceramic district compared to previous years. The OHPs reported an increase in muscular-skeletal complaints, gastritis, tension-type headache, irritable bowel syndrome symptoms, back pain, panic attacks, insomnia, tachycardia, and other medically unexplained symptoms. Anxiety problems seemed to prevail over depressive manifestations. An increase was reported for antidepressants and benzodiazepines consumption. Conclusions: The local impact of the economic crisis on health was mainly negative, consistent with available national data. Mental health professionals could work together with OHPs, e.g., through Balint Group-like meetings, to develop targeted psychosocial and clinical interventions addressing the medical, psychological and social needs of workers, also involving advocacy and fostering workers’ empowerment.